Physiological, biochemical and genetic bases of amaranth (Amaranthus L.) breeding for food and feed purposes (a review) - A. B. Shcherban (Труды по прикладной ботанике, генетике и селекции, 2020)
The review gives an insight into amaranth, a very promising crop for the whole world. This crop has a long history dating back to the days of the Aztecs and Incas, for whom it was one of the most important crops, along with corn. However, unlike the latter, amaranth lost its nutritional value after being introduced into Europe. Only in the 20th century, largely thanks to Nikolai Vavilov, amaranth attracted great interest as a food and feed crop. Amaranth is a plant unique in its nutritional properties. It is characterized by a high content of protein saturated with essential amino acids, especially lysine, and a large number of bioactive compounds, such as vitamin C, amaranthine, rutin, carotenoids, etc. Of particular value is grain oil saturated with various lipid compounds: squalene, vitamin E, phytosterols, and fatty acids. These lipid compounds have a number of important properties from the point of view of functional nutrition: as natural antioxidants they bind free radicals, normalize lipid metabolism, and help to decrease blood cholesterol levels. The review focuses on genes that determine the content of the main, valuable biochemical components: squalene, vitamin C, and lysine. The genetic pathways that control the biosynthesis of these components have been studied in detail in various model plant objects. The presence of the complete genomic sequence of Amaranthus hypochondriacus L. makes it possible to identify orthologs of key biosynthetic genes. At the moment, only few genes in amaranth have been identified, including the squalene synthase (SQS) gene, the VTC2 ascorbic acid synthesis gene, and the key genes for lysine synthesis – AK and DHDPS. The article discusses the prospects and trends of marker-assisted selection of this crop as well as the difficulties of its systematization and genotyping, which have to be overcome to successfully solve plant breeding problems.